1999
DOI: 10.1161/01.hyp.33.6.1399
|View full text |Cite
|
Sign up to set email alerts
|

Increased Chymase-Dependent Angiotensin II Formation in Human Atherosclerotic Aorta

Abstract: Abstract-Locally formed angiotensin II (Ang II) and mast cells may participate in the development of atherosclerosis.Chymase, which originates from mast cells, is the major Ang II-forming enzyme in the human heart and aorta in vitro.The aim of the present study was to investigate aortic Ang II-forming activity (AIIFA) and the histochemical localization of each Ang II-forming enzyme in the atheromatous human aorta. Specimens of normal (nϭ9), atherosclerotic (nϭ8), and aneurysmal (nϭ6) human aortas were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
3
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(151 citation statements)
references
References 43 publications
3
143
3
2
Order By: Relevance
“…There is recent experimental evidence that up to 40% of tissue AII in the blood vessels, heart and kidneys is produced through the alternate pathway, mostly through the action of chymase and other enzymes. [34][35][36] This could account for the fact that AII levels after being suppressed initially by ACE inhibitors begin to rise later and almost return to baseline levels. 37 For these reasons, ARBs should be, perhaps, the preferred drugs for initiating antihypertensive therapy or even substituting previous treatment with ACE inhibitors.…”
Section: Angiotensin Receptor Blockers Vs Angiotensin-converting Enzymentioning
confidence: 99%
“…There is recent experimental evidence that up to 40% of tissue AII in the blood vessels, heart and kidneys is produced through the alternate pathway, mostly through the action of chymase and other enzymes. [34][35][36] This could account for the fact that AII levels after being suppressed initially by ACE inhibitors begin to rise later and almost return to baseline levels. 37 For these reasons, ARBs should be, perhaps, the preferred drugs for initiating antihypertensive therapy or even substituting previous treatment with ACE inhibitors.…”
Section: Angiotensin Receptor Blockers Vs Angiotensin-converting Enzymentioning
confidence: 99%
“…We have reported that Ang II is generated from Ang I by two distinct types of Ang II-forming enzymes, angiotensin converting enzyme (ACE) and chymase in human cardiovascular tissues (19,20), and that ACE and chymase are associated with the development of atherosclerosis (8,20,21). Ihara et al (22) reported that the ratio of chymase-dependent Ang II-forming activity to total Ang IIforming activity was significantly higher in the aneurysmal aortae (94.8%) than in the normal aortae (85.6%). Furthermore, they also reported significant increases in chymase-dependent Ang II-forming activity in the aneurysmal aortae.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the efficacy of the combination of DRIs and ARBs might not be sufficiently evaluated. As ACE escape or angiotensin II production via non-ACE pathways could compromise the effect of ACEIs on the RAS, [40][41][42] the combination of DRIs and ARBs might be beneficial.…”
Section: Discussionmentioning
confidence: 99%